(untitled) (London, 2013)
The skills boxes that appear throughout the books signal the topic focus to the teacher, while providing the students with relevant tips, words and phrases. The study skills focus develops this further, providing students with practical guidance and support, and building confidence for independent learning throughout their university career
Keywords: Tiếng Anh,English language,English language,Tiếng Anh; Viết,Listening,Spoken english,Nghe